Amphiregulin as a novel diagnostic and prognostic biomarker of hepatocellular carcinoma before and after locoregional treatment - Amira Isaac (SpringerOpen, 2021)
Abstract Background Hepatocellular carcinoma is a highly prevalent tumor worldwide. Amphiregulin is a ligand of the epidermal growth factor receptor. Its elevation is linked to different inflammatory and neoplastic conditions. Therefore, amphiregulin may represent a potential diagnostic target in HCC, which has sparked interest as a potential predictor of diagnosis and progression of HCC. The current work was set out to evaluate amphiregulin as a possible diagnostic and prognostic biomarker for HCC on top of cirrhosis. Thirty adult patients with liver cirrhosis and HCC (HCC group) were randomly selected as candidates for locoregional therapies, either radiofrequency ablation or transarterial chemoembolization. A separate group of thirty liver cirrhosis patients served as controls (cirrhosis group). All patients underwent standard laboratory tests and abdominal ultrasounds. Alpha-fetoprotein and amphiregulin were measured twice at baseline and 1 month after the intervention. Results Baseline serum amphiregulin was significantly higher in the HCC group than in the cirrhosis group (23.2 ± 11.5 vs. 11.1 ± 7.1), with a p value < 0.001. Patients with multiple and larger focal lesions had greater levels of amphiregulin, with p values of 0.015 and 0.002, respectively. At 1 month following locoregional treatment, the amphiregulin level considerably declined compared with its baseline levels (from 23.2 ± 11.5 to 19.4 ± 10.9), with a p value of 0.012, while AFP showed an insignificant reduction. At follow-up, the level of serum amphiregulin was statistically significantly greater in recurrence cases than in remission cases (30.8 ± 14.1 vs. 17.2 ± 8.8), with a p value of 0.008, and the same was observed for AFP level. At a cutoff ≥ 17 pg/mL, amphiregulin was a valuable marker in HCC detection with a sensitivity and specificity of 63.3% and 86.7%, respectively, while it has 60% sensitivity and 96% specificity in detecting possible tumor recurrence at a cutoff ≥ 29.7 pg/ml. Conclusions Amphiregulin may be a good diagnostic marker for HCC and a prognostic marker after locoregional therapies because its follow-up levels are useful in predicting possible tumor recurrence.